Metode-Metode Dalam Pembelajaran Keterampilan Bahasa Arab Reseptif - R. Umi Baroroh; Fauziyah Nur Rahmawati (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2020)
There are four main components in learning Arabic language, as the basis .They are listening (istima), reading (qiroah), speaking (kalam), and writing skills (kitabah). Istima 'and qiroah skills are receptive skills. This research is aimed to find out how to choose suitable methods to be applied in Arabic learning in receptive skills. This research is library research (literature study) that relies on books or journals, and then the data was analyzed using the content analysis method. The findings of this study indicate that there are many methods in learning Arabic, including direct method, aAl-sam'iyah al-syafawiyah, qiroah, and teacher silent method. This research also discusses how to use a good method to make students do not find difficulties and boring in the learning and the aim learning is achieved. In selecting a method, the teacher should know how the students’ condition and development.